Socio-demographic and health characteristics of elderly individuals: support for health services Características sociodemográficas y de salud de ancianos: contribuciones para los servicios de salud Características sociodemográficas e de saúde de idosos: contribuições para os serviços de saúde - Calíope Pilger; Mario Humberto Menon; Thais Aidar de Freitas Mathias (Universidade de São Paulo, 2011)
This is a sectional epidemiological study including a household survey. It describes the socio-demographic and health conditions of elderly individuals residing in Guarapuava, PR, Brazil. The study's sample consisted of 359 elderly individuals enrolled in primary health care units in the city. Interviews were conducted from January to April 2010 using sections I and II of the Brazil Old Age Schedule questionnaire. The results revealed that most interviewees were women (64.3%), health self-perception was considered 'good' by 54.6%, and the most prevalent diseases were hypertension (34.9%), diabetes mellitus (12,4%) and arthritis/arthrosis (12.2%). Most elderly individuals use dental prostheses (74.4%) and 56.5% wear glasses or contact lenses. The conclusion is that knowledge concerning the social, demographic, and health profiles of these individuals favors the implementation of actions specific to this age group by health providers, and helps managers to develop health indicators. Se trata de un estudio epidemiológico seccional con encuesta domiciliar con el objetivo de describir las características sociodemográficas y las condiciones de salud de ancianos del municipio de Guarapuava, PR, Brasil. La muestra del estudio fue compuesta por 359 ancianos inscritos en las UBS del municipio. Las entrevistas fueron realizadas de enero a abril de 2010 utilizando la sección I y II del cuestionario Brasil Old Age Schedule - BOAS. Los resultados demostraron que el sexo femenino fue prevalente (64,3%), la autopercepción de salud fue buena para 54,6% de los ancianos; las enfermedades más relatadas fueron hipertensión (34,9%), diabetes mellitus (12,4%) y artritis/artrosis (12,2%). La mayoría de los ancianos utiliza prótesis dentaria (74,4%), 56,5% lentes o lente de contacto. Se concluye que el conocimiento del perfil sociodemográfico y de salud de estos ancianos favorece la implantación de acciones específicas, para este intervalo etario, por los profesionales de salud que trabajan en este municipio, además de auxiliar a los gestores para formular indicadores de salud. Trata-se de estudo epidemiológico seccional com inquérito domiciliar, com o objetivo de descrever as características sociodemográficas e as condições de saúde de idosos do município de Guarapuava, PR, Brasil. A amostra do estudo foi composta por 359 idosos inscritos nas UBSs do município. As entrevistas foram realizadas de janeiro a abril de 2010, utilizando-se a seção I e II do questionário Brazil Old Age Schedule - BOAS. Os resultados demonstraram que o sexo feminino foi prevalente (64,3%), a autopercepção de saúde foi boa para 54,6% dos idosos, as doenças mais relatadas foram hipertensão (34,9%), diabetes mellitus (12,4%) e artrite/artrose (12,2%). A maioria dos idosos utiliza prótese dentária (74,4%), 56,5% óculos ou lente de contato. Conclui-se que o conhecimento do perfil sociodemográfico e de saúde desses idosos favorece a implantação de ações específicas para essa faixa etária pelos profissionais de saúde que trabalham nesse município, além de auxiliar os gestores para formular indicadores de saúde.